Níveis de glicose in ovo sobre parâmetros de incubação e desempenho de codornas de corte - Yara Cardoso Braga (2024)
In ovo nutrition is an emerging technique in poultry farming that aims to improve embryonic development and post-hatch performance by administering nutrients directly into the egg during the incubation period. Among the various substances tested, glucose has been explored due to its fundamental role in energy metabolism. The aim of this study was to evaluate the inclusion of glucose in broiler quail eggs during the pre-hatch phase, and its impact on performance and post slaughter carcass yield. A total of 1200 broiler quail eggs from two genetic groups were incubated. On the 14th day of incubation, after removing the eggs without embryonic development through ovoscopy, the eggs were distributed into five treatments (inoculation of 0; 8; 16; 24 and 32mg of 50% glucose). Each concentration of glucose was diluted in 0.9% saline solution to make up 0.1ml of nutrient solution. The nutrient solution was inoculated into the egg's allantois using disposable syringes and needles. Hatchability and mortality rate were assessed by embryodiagnosis. After hatching, body weight, weight gain, feed consumption and feed conversion were assessed up to 35 days of age, as well as carcass yield and edible organs, which were measured and subjected to analysis of variance. The entire experiment was carried out in a completely randomized design, in a 5x2 factorial arrangement (five treatments x two genetic groups). There was no significant effect (P>0.0.5) for the variables analyzed. Glucose, at doses of 0 to 32mg, applied to the allantoic cavity on the 14th day of incubation, did not interfere with embryonic development or the productive performance of broiler quails.